Effect of a prospective opioid reduction intervention on opioid prescribing and use after radical prostatectomy: results of the Opioid Reduction Intervention for Open, Laparoscopic, and Endoscopic Surgery (ORIOLES) Initiative. (15th November 2019) - Patel, Hiten D.; Faisal, Farzana A.; Patel, Neil D.; Pavlovich, Christian P.; Allaf, Mohamad E.; Han, Misop; Herati, Amin S.
Abstract : Objectives: To evaluate the effect of a prospective opioid reduction intervention after radical prostatectomy (RP; based on a surgery‐specific guideline and education) on post‐discharge opioid prescribing, use, disposal, and need for additional opioid medication. Patients and Methods: A prospective, non‐randomised, pre–post interventional trial of patients undergoing RP for prostate cancer (August 2017–November 2018) was conducted as part of the Opioid Reduction Intervention for Open, Laparoscopic, and Endoscopic Surgery (ORIOLES) Initiative. An evidence‐based intervention including: a discharge sheet, nursing education, and standardised prescribing guideline, was applied with the primary outcome of total oral morphine equivalents (OMEQ) used after RP. Secondary outcomes included opioid prescribing, opioid disposal, need for additional opioid medication, and presence of incisional/post‐surgical abdominal pain at 30 days after RP. Results: A total of 214 (Pre‐Intervention arm) and 229 (Post‐Intervention arm) adult patients were enrolled (100% follow‐up). The intervention reduced post‐discharge opioid prescribing (from 224.3 to 120.3 mg; −46.4%, P  = 0.01), reduced opioid use (from 52.1 to 38.3 mg; −26.5%, P  < 0.01), and increased opioid disposal (+13.5%, P  < 0.01). Greater prescribing of opioids at discharge, higher body mass index, and use of opioid medication prior to surgery, were independently associated with greater post‐discharge opioid use, while history of a chronic pain diagnosis was not statistically significant. In the Post‐Intervention cohort, 2.2% of patients needed additional medication for post‐surgical pain (0.9% obtained a prescription) and 1.3% initiated long‐term use. Conclusions: A prospective, evidence‐based intervention reduced post‐discharge opioid prescribing and use, while increasing disposal after RP. Risk factors for increased opioid use were identified. The results support expanding the use of evidence‐based opioid reduction interventions to other surgical specialties.